2022
DOI: 10.1101/2022.09.29.510040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

QUAS-R: Glutamine (Q) Uptake Assay with Single cell Resolution reveals metabolic heterogeneity with immune populations

Abstract: System level analysis of single cell data is rapidly transforming the field of immunometabolism. However, metabolic profiling of single cells and small populations by flow and mass cytometry is extremely limited by the availability of specific reagents such as antibodies and fluorescently nutrient analogues. Given the competitive demand for nutrients in pathogenic microenvironments including sites of infection, tumours and autoinflammation, there is a need to understand how and when immune cells access these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…1D-E). We also performed immunostaining for the amino acid transporter ASCT2, the main transporter of Asn and which also transports L-AHA 13,26 , and found high expression in GC B cells, more pronounced in the DZ like ASNS (Fig. 1M and Extended Data 1F).…”
Section: Gc B Cells Have Highly Active Protein Synthesis and Asparagi...mentioning
confidence: 97%
See 2 more Smart Citations
“…1D-E). We also performed immunostaining for the amino acid transporter ASCT2, the main transporter of Asn and which also transports L-AHA 13,26 , and found high expression in GC B cells, more pronounced in the DZ like ASNS (Fig. 1M and Extended Data 1F).…”
Section: Gc B Cells Have Highly Active Protein Synthesis and Asparagi...mentioning
confidence: 97%
“…2A). HPG is then fluorescently labelled using Click chemistry, and its uptake measured by flow cytometry 26 . We found that there was clear dose-dependent competition between HPG and Asn in GC B cells and plasmablasts (Fig.…”
Section: B Cells Require Asns When the Availability Of Asn Is Limitedmentioning
confidence: 99%
See 1 more Smart Citation
“…In BONCAT, cells are incubated with a non-canonical amino acid (ncAA) analog containing a minimal chemical modification, which can subsequently be targeted to fluorescently tag nascent proteins through copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) (11), more commonly known as the 'click' reaction. Among others, BONCAT has been used for affinity purification of nascent proteins (12), to track and localize the newly synthesized proteins in cells (13), and to measure SLC1A5-mediated amino acid uptake (14). A significant advantage of employing BONCAT for measuring protein synthesis is that ncAAs are non-toxic (15).…”
Section: Introductionmentioning
confidence: 99%